2021
DOI: 10.1111/tpj.15492
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450‐catalyzed biosynthesis of furanoditerpenoids in the bioenergy crop switchgrass (Panicum virgatum L.)

Abstract: Specialized diterpenoid metabolites are important mediators of plant-environment interactions in monocot crops. To understand metabolite functions in plant environmental adaptation that ultimately can enable crop improvement strategies, a deeper knowledge of the underlying species-specific biosynthetic pathways is required. Here, we report the genomics-enabled discovery of five cytochrome P450 monooxygenases (CYP71Z25-CYP71Z29) that form previously unknown furanoditerpenoids in the monocot bioenergy crop Panic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Although likely the result of convergent evolution, furan rings are found in a variety of natural products ( 36, 37 ). Although furan-forming enzymes have been reported from other plants ( 38, 39 ), ( 40 ), the AKR, CYP716AD and 2-ODD module described here represents a new mechanism of furan formation via the oxidative cleavage of a C-4 moiety. Along with the sterol isomerases (MOIs), the AKR and 2-ODDs add to the growing pool of enzyme families ( 41, 42 ) associated with primary sterol metabolism that appear to have been recruited to plant secondary triterpene metabolism, possibly due to the structural similarities between sterols and tetracyclic triterpenes.…”
Section: Discussionmentioning
confidence: 83%
“…Although likely the result of convergent evolution, furan rings are found in a variety of natural products ( 36, 37 ). Although furan-forming enzymes have been reported from other plants ( 38, 39 ), ( 40 ), the AKR, CYP716AD and 2-ODD module described here represents a new mechanism of furan formation via the oxidative cleavage of a C-4 moiety. Along with the sterol isomerases (MOIs), the AKR and 2-ODDs add to the growing pool of enzyme families ( 41, 42 ) associated with primary sterol metabolism that appear to have been recruited to plant secondary triterpene metabolism, possibly due to the structural similarities between sterols and tetracyclic triterpenes.…”
Section: Discussionmentioning
confidence: 83%
“…In addition to predicted phospholipids, a few features were enriched in Alamo leaves under drought stress, whereas many unidentified compounds were enriched in drought-treated Cave-in-Rock leaves (Supporting Information Table S2). In contrast, several compounds identified as diterpenoids and triterpenoids by comparison of RT and fragmentation patterns to previously identified compounds (Li et al, 2020;Muchlinski et al, 2021) accumulated in roots of both Alamo and Cave-in-Rock plants under drought stress, with a stronger increase in Alamo (Fig. 7).…”
Section: Switchgrass Leaves and Roots Show Drought-inducible Metaboli...mentioning
confidence: 81%
“…Our prior research identified expansive, species-specific diterpene synthase (diTPS) and P450 families in switchgrass that form complex metabolic networks toward a range of labdane-related diterpenoids, including syn -pimarane and furanoditerpenoid compounds that occur, perhaps uniquely, in switchgrass (Fig. S5) (Pelot et al 2018; Muchlinski et al 2021). This pathway knowledge enabled a detailed analysis of transcriptomic alterations related to diterpenoid metabolism.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations